Association Between Subclinical Magnesium Deficiency and Major Cardiovascular Events: A Systematic Review and Meta-Analysis - Khan, Zarmina; Roffa; Khan, Junaid Ayaz; Sharif, Muhammad Imran; Basra, Ayesha Amir; Sanaullah; Atif, Aima; Nixon, Cathrine; Khan, Saman; Das, Binayok (Indus Journal of Bioscience Research, 2025)
Background: Subclinical magnesium deficiency has emerged as a potential modifiable factor in cardiovascular disease (CVD) risk. Although previous studies have examined its association with adverse cardiovascular outcomes, findings remain inconsistent. This systematic review and meta-analysis aimed to evaluate the association between subclinical magnesium deficiency and the risk of major cardiovascular events. Methods: A comprehensive literature search was conducted using PubMed, Scopus, Embase, and Web of Science from January 2000 to March 2024. Observational studies assessing the relationship between subclinical magnesium deficiency and outcomes including coronary heart disease (CHD), sudden cardiac death (SCD), stroke, and cardiovascular mortality were included. Data extraction, quality assessment (using NOS and AXIS tools), and meta-analysis were performed according to PRISMA guidelines. Pooled hazard ratios (HRs) or odds ratios (Ors) with 95% confidence intervals (Cis) were calculated using a random-effects model. Results: Three studies with a total of 56,448 participants met the inclusion criteria. Subclinical magnesium deficiency was significantly associated with an increased risk of CHD mortality (HR = 1.36, 95% CI: 1.09–1.69), sudden cardiac death (HR = 1.54, 95% CI: 1.12–2.11), cardiovascular mortality (HR = 2.01, 95% CI: 1.49–2.71), and stroke incidence (OR = 1.96, 95% CI: 1.55–2.49). Additionally, each standard deviation increase in serum magnesium level was associated with 21% lower odds of composite cardiovascular events (OR = 0.79, 95% CI: 0.70–0.89). The included studies exhibited low statistical heterogeneity, and funnel plots showed no significant publication bias. Conclusion: This meta-analysis provides strong evidence that subclinical magnesium deficiency is independently associated with elevated risk of major cardiovascular events. Routine assessment of magnesium status may serve as a cost-effective tool for early identification of at-risk individuals. Further randomized trials are warranted to evaluate the therapeutic impact of magnesium supplementation in cardiovascular prevention.